The other exchange : women, servants, and the urban underclass in early modern English literature - Van Renen, Denys (Early modern cultural studies, 2017)
"The Other Exchange investigates the ways in which English literature represents women, masterless men, and foreigners in the economic and sociocultural foundation of the development of middle-class consciousness in early modern England"--